Militarizing Youth In Public Education: Observations from A Military-Style Charter School - Aguirre, Adalberto (Social justice, 2005)
Part of a special issue on challenging corporate control of schools and communities. The writers describe a military-style charter school. Suggesting that the charter school serves as a context for examining the utility of transferring neoliberal values into school practices, they focus on the charter school as a vehicle for the military indoctrination and recruitment of youth. They define the school as one response to pressure from proponents of neoliberal values and the market-driven mindset.